Total Cholesterol and Triglyceride Levels after Giving Olive Oil and Fig Fruid Extract Against Rattus Novergicus With High-Fat Diet - Sulastri, Evi; Syamsu, Rachmat Faisal; Karim, Marzelina; Royani, Ida; Karim, Abdul Mubdi Ardiansar Arifuddin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The reserach entiled “Changes in total cholesterol levels and trigelyceride levels after administration of olive oil and fig leaf extract“ was conducted from July to September 2023. This study aims to determine changes in total cholesterol levels and triglyceride levels when given olive oil and fig friut extract to white mice on a high-fat diet. This research method use an experimental quantitative research type with a pretest-posttest control group research design then analyzed through statistical analysis test using the Microsoft Office Excel 2013 application. Based on the results of study, constant result was obtained for total cholesterol in all treatment groups, namely 86.5 mg/dL and significant results were obtained in reducing triglycerides in the olive oil treatment group and the combination of olive oil and fig fruit extract, namely in the group given olive oil of 170.5 mg. /dL (81.19%), in the group given a combination of fig fruit extract it was 43.75 mg/dL (38.55%), and the increase in the group given fig fruit extract was 38 mg/dL (29.92%). The combination of olive oil and fig fruit extract has a constant effect on total cholesterol levels and reduces triglyceride levels. Fig fruit extract has a constant effect on total cholesterol levels and increases triglyceride levels. Olive oil has a constant effect on total cholesterol levels and more significant results in reducing triglyceride levels in mice with high-fat feed in all treatment groups.